2006
DOI: 10.1177/1473325006070291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Social Work Practice in Teams Using a Video Vignette Technique in a Multi-method Design

Abstract: English This article focuses on the use of the vignette method in social worker teams and thereby collective or shared aspects of practice, which cannot be reached through a presentation of a vignette separately to the individual members of the team. A video vignette case was presented to four social worker teams in connection with a focus group session in order to compare the teams’ assessment of the client. The negotiations in the focus groups accentuate how teams interpret the same client in different ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
15
0
2
Order By: Relevance
“…While there are many advantages in using vignettes to research topics that might not necessarily be accessible to the researcher, the most frequently identified limitation surrounds the distance between responses to vignettes and social reality (Eskelinen and Caswell, 2006). There is no guarantee that the responses given will mirror behaviour of respondents in their professional practice (Wilks, 2004, p. 82).…”
Section: Vignettesmentioning
confidence: 99%
See 3 more Smart Citations
“…While there are many advantages in using vignettes to research topics that might not necessarily be accessible to the researcher, the most frequently identified limitation surrounds the distance between responses to vignettes and social reality (Eskelinen and Caswell, 2006). There is no guarantee that the responses given will mirror behaviour of respondents in their professional practice (Wilks, 2004, p. 82).…”
Section: Vignettesmentioning
confidence: 99%
“…The benefits of the use of vignettes in this study are that they are administered across a wide range of settings; will elicit responses at time one and time two (beginning and end of degree-level study); and results will be available for comparison with other studies (Benner, 1984;Fook et al, 2000). Eskelinen and Caswell (2006) found that vignettes created a shared point of departure and, by following up observations and discussions, they could discern differences in approach that could be attributed to institutional and social contexts. By focusing on responses that will reflect developments in professional approaches, it is anticipated that the analysis of the vignettes will produce rich data on differences that emerge as a result of degree-level study which will also be considered in the light of data from questionnaires to practice teachers/assessors, interviews with key informants such as employers and self-reports from students in focus groups at the case study sites and in the online survey.…”
Section: Vignettesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently identified limitations to vignette studies are related to the distance between the responses to vignettes and social reality, since there is no guarantee that the responses will mirror the behavior of the respondents in their professional practice (Eskelinen & Caswell, 2006;Wilks, 2004:82). However, in this study the vignettes create an important shared point of departure and may reveal differences in approach that could be attributed to institutional and social contexts (Soydan, 1995;1996;Eskelinen & Caswell, 2006).…”
Section: The Vignette Methodsmentioning
confidence: 99%